TANGGUNG JAWAB MUDHARIB TERHADAP KERUGIAN DALAM MUDHARABAH PERSEFEKTIF FIQH MUAMALAH - Wahyu Alilia , Valentina; Cahyani, Dian Dwi; Ananda Santosa, Salsabila Fitri; Arifah, Mufaida Shofia; Waluyo (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This research discusses the concept of mudharib (fund manager) responsibility for losses in mudharabah contracts from the perspective of muamalah fiqh and its implementation in contemporary Islamic banking practices. This research uses a qualitative method with a literature study approach. The results show that in principle, mudharib is not responsible for losses as long as the losses are not the result of negligence, breach of contract, or betrayal of trust. However, if there is an act of ta'addi (abuse of authority), taqsir (negligence), or mukhalafah ash-syarth (violation of the contract), then the mudharib is obliged to bear the losses incurred. The views of scholars from the four schools of fiqh agree on this principle, although there are variations in the aspects of proof. In modern Islamic banking practice, there are developments in the form of applying guarantees and strict supervision as a risk mitigation effort. This concept must still be carried out in accordance with the principles of sharia and maqashid sharia in order to maintain justice, trust, and protection of property.